Pandemic distress associated with segregation and social stressors - Turpin, Rodman; Giorgi, Salvatore; Curtis, Brenda (Frontiers in Public Health, 2023)
Background: Racial/ethnic minorities are disproportionately impacted by the COVID-19 pandemic, as they are more likely to experience structural and interpersonal racial discrimination, and thus social marginalization. Based on this, we tested for associations between pandemic distress outcomes and four exposures: racial segregation, coronavirus-related racial bias, social status, and social support. Methods: Data were collected as part of a larger longitudinal national study on mental health during the pandemic (n=1,309). We tested if county-level segregation and individual-level social status, social support, and coronavirus racial bias were associated with pandemic distress using cumulative ordinal regression models, both unadjusted and adjusted for covariates (gender, age, education, and income). Results: Both the segregation index (PR=1.19; 95% CI 1.03, 1.36) and the coronavirus racial bias scale (PR=1.17; 95% CI 1.06, 1.29) were significantly associated with pandemic distress. Estimates were similar, after adjusting for covariates, for both segregation (aPR=1.15; 95% CI 1.01, 1.31) and coronavirus racial bias (PR=1.12; 95% CI 1.02, 1.24). Higher social status (aPR=0.74; 95% CI 0.64, 0.86) and social support (aPR=0.81; 95% CI 0.73, 0.90) were associated with lower pandemic distress after adjustment. Conclusions: Segregation and coronavirus racial bias are relevant pandemic stressors, and thus have implications for minority health. Future research exploring potential mechanisms of this relationship, including specific forms of racial discrimination related to pandemic distress and implications for social justice efforts, are recommended.